2020
DOI: 10.1111/jcal.12436
|View full text |Cite
|
Sign up to set email alerts
|

Digital collaborative learning in elementary and middle schools as a function of individualistic and collectivistic culture: The role of ICT coordinators' leadership experience, students' collaboration skills, and sustainability

Abstract: The purpose of this study was to examine the influence of online collaborative learning experiences on students' digital collaboration skills and on the sustainability of e‐collaboration in schools' culture—comparing individualistic versus collectivistic cultures. In addition, we explored how the leadership experience of schools' ICT coordinators was predicted by their sense of professionalism and cognitive, emotional and social aspects of perceived learning (PL), while leading the collaborative projects. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 36 publications
2
33
0
Order By: Relevance
“…It should be borne in mind that the collaborative method promotes learning in a sustainable development context, which is essential in these times [51][52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be borne in mind that the collaborative method promotes learning in a sustainable development context, which is essential in these times [51][52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it can be indicated that the application of collaborative teaching methods promotes sustainability [51]. An example of this is the European Project Semester (EPS) programme, which encourages multidisciplinary and multicultural teamwork and increases the ability to communicate, problem-solve, creativity, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of Arab and Jewish students in Israel study in separate school systems (Birenbaum, Nasser, & Tatsuoka, 2007; Mittelberg, Rozner, & Forgasz, 2011) and teacher‐education colleges. There are gaps between the schools serving the different cultures in budgets, infrastructure, programs and performance, (Blau, Shamir‐Inbal, & Hadad, 2020; Hadad Haj‐Yahya & Rudnitzky, 2018).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…This methodology encourages the development of other skills in students, such as interaction, communication, problem solving, motivation, sense of community, and autonomy, among other aspects [38][39][40][41][42][43][44][45][46][47][48][49]. In addition, the collaborative learning method promotes and facilitates the acquisition of knowledge in areas of study where sustainable development is essential [65][66][67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it should be noted that studies indicate that the collaborative learning method favors sustainability, especially if this method is developed digitally [65] In addition, collaborative learning, associated with specific sustainability programs such as the European Project Semester (EPS), promotes multicultural and multidisciplinary teamwork, communication, problem solving, creativity, leadership, entrepreneurship, ethical reasoning, and global contextual analysis [66]. The collaborative learning method has been applied in the training of students of various kinds, especially students of interior design [67], administrative studies [68], or agro-food systems [69], with a view to sustainable development.…”
Section: Theoretical Backgroundmentioning
confidence: 99%